The Performance of Non-Impaired Tamil-English Bilinguals on the Bilingual Aphasia Test - Sanjeevan, Teenu (My University, 2012)
This thesis examines the performance of non-impaired Tamil-English speaking bilinguals on the Tamil-English version of the Bilingual Aphasia Test (BAT) (Paradis and Libben, 1987). The test was administered to 25 participants, 15 women and 10 men. The results show that, on average, participants achieved an overall score of 97%. However, participants did not do well on two subtests on the English version, specifically sections on derivational morphology and morphological opposites. Also, a more detailed analysis indicates that years of education significantly correlates with performance, even though it is claimed that years of education should not affect performance on this test. This study makes suggestions for how to improve the Tamil-English version, in view of the findings from this study, and provides a cautionary note on the role played by years of education in test performance. If the latter factor is not taken into account, the test could possibly lead to an inaccurate assessment of a patient’s language abilities, and could potentially result in misdiagnosis. In an effort to increase the test’s validity and reliability, this study recommends a series of modifications to the Tamil-English version of the BAT, based both on participants’ comments and on statistical analyses.
Keywords: Tamil-English; Bilingual Aphasia Test; Non-Impaired; Health and Medical Administration; Rehabilitation and Therapy; South and Southeast Asian Languages and Societies; Health and Medical Administration